American English file : Teacher's book 2 - Koenig, Chistina Latham; Oxenden, Clive; Seligson, Paul (Oxford Oxford University Press, 2013)
With grammar, vocabulary, and pronunciation practice in every lesson, students are equipped with a solid foundation for successful speaking
Keywords: Khoa học cơ bản